1985
DOI: 10.1143/jjap.24.1224
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Radiation Resistance of Pure Silica Core Fibers by Hydrogen Treatment

Abstract: A pure silica core fiber with glass cladding is known to produce larger absorption in the visible wavelength region under γ-ray irradiation than a similar fiber with silicone cladding. This absorption is a serious problem, especially in image-guiding fibers used in radiation environments such as in nuclear power plants. The absorption is attributed to the formation of defect centers such as non-bridging oxygen hole centers and E' centers induced by bond scission. A new and simple method of hydrogen treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…Later, Nagasawa [9] observed a similar effect in irradiated glass fibres. The author observed that the hydrogen treatment, carried out either prior to or following the irradiation, drastically suppressed the 2 eV optical absorption band that develops in silica due to the formation of non-bridging oxygen hole centres (NBOHC) and Peroxy radicals (POR).…”
Section: Role Of Hydrogen In Irradiated Silica Glassesmentioning
confidence: 73%
See 1 more Smart Citation
“…Later, Nagasawa [9] observed a similar effect in irradiated glass fibres. The author observed that the hydrogen treatment, carried out either prior to or following the irradiation, drastically suppressed the 2 eV optical absorption band that develops in silica due to the formation of non-bridging oxygen hole centres (NBOHC) and Peroxy radicals (POR).…”
Section: Role Of Hydrogen In Irradiated Silica Glassesmentioning
confidence: 73%
“…The author observed that the hydrogen treatment, carried out either prior to or following the irradiation, drastically suppressed the 2 eV optical absorption band that develops in silica due to the formation of non-bridging oxygen hole centres (NBOHC) and Peroxy radicals (POR). In 1992, Lyons and Looney [9] investigated the radiation-induced loss response at only one wavelength (850 nm) in different hydrogenated fibres. The authors explained that the combination of the pre-irradiation sequence at moderate total dose followed directly by the hydrogen loading phase contributes to reduce the number of preexisting defects and/or weak bonds that would otherwise act as precursors of colour centres during subsequent irradiation.…”
Section: Role Of Hydrogen In Irradiated Silica Glassesmentioning
confidence: 99%
“…Optical absorption shorter than 400 nm was ascribed to E 0 center and that at 630 nm was ascribed to non-bridging oxygen hole centers (NBOHC). [8,9]. The irradiation time dependence at 400 and 630 nm is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The basic attenuation of these fibers is generally acceptable. The induced losses, primarily comes from transient or permanent changes in the silica, which are due to nonlinearities arising from two photon absorption [4].…”
Section: Introductionmentioning
confidence: 99%